2004
DOI: 10.1080/0014013042000193273
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics modelling and evaluation of automobile seat comfort

Abstract: Automobile seats are developed in an iterative manner because subjective feedback, which is usually of questionable quality, drives the design. The time and cost associated with iteration could be justified if the process was guaranteed to produce a comfortable seat. Unfortunately, this is not the case. Current practices are based on the premise that seat system design teams need objective, measurable laboratory standards, which can be linked to subjective perceptions of comfort. Only in this way can predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 19 publications
1
43
0
1
Order By: Relevance
“…It is essential that researchers formalize the implied relationship by developing predictive instruments linking performance measures (obtained through scientifically sound and standardized methodologies) to subjective perceptions of comfort (derived from a questionnaire with proven levels of reliability and validity). Modeling alternatives include statistical techniques (Kolich and Taboun, 2004) and artificial neural networks (Kolich, 2004). The models may ARTICLE IN PRESS also be improved by considering the previously described social factors.…”
Section: Model Subjective Perceptions Of Comfort As a Function Of Permentioning
confidence: 99%
“…It is essential that researchers formalize the implied relationship by developing predictive instruments linking performance measures (obtained through scientifically sound and standardized methodologies) to subjective perceptions of comfort (derived from a questionnaire with proven levels of reliability and validity). Modeling alternatives include statistical techniques (Kolich and Taboun, 2004) and artificial neural networks (Kolich, 2004). The models may ARTICLE IN PRESS also be improved by considering the previously described social factors.…”
Section: Model Subjective Perceptions Of Comfort As a Function Of Permentioning
confidence: 99%
“…Most sitting force studies have been focused mainly on static sitting for sitters weighing less than 136 kg, in wheelchair research (Gilsdorf et al 1990;Gilsdorf et al 1991;Aissaoui et al 2001;Chou et al 2002) and vehicle seat design (Rakheja et al 2002;Kolich 2004;Kolich and Taboun 2004;Tarczay 2005;Bush and Hubbard 2007;Moes 2007). Sitting force studies were also found in sitting comfort research with emphasis on sitting pressure distribution on a seat (Chow and Odell 1978;Drummond et al 1982;Bush and Hubbard 2007), which data can be converted to sitting forces.…”
Section: Introductionmentioning
confidence: 98%
“…That late sensory validation is part of the trial-and-error method. Kolich and Taboun (2004) illustrate this iterative manner on the automobile seats design case. Integrating user requirements into preliminary design ensures less iterations in the design process.…”
Section: Introductionmentioning
confidence: 99%